Waktu Gesek Terhadap Kekuatan Tarik Sambungan AA6061-Baja Karbon Pada Pengelasan Gesek Continuous Drive - Jack C.A. Pah; Defmit B.N. Riwu; Dominggus Adoe; Adi Y. Tobe (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
The objective of this research was to get the effect of friction time on the tensile strength of the joining of aluminum alloy AA6061 and carbon steel, with continuous drive friction welding process. Variations of friction time of this research were 5 seconds, 7 seconds, 9 seconds, and 11 seconds. Other friction welding variables were friction pressure 24 MPa, forging pressure 79 MPa, forging time 60 seconds, and friction rotation speed 1600 rpm. The independent variable was the ultimate tensile strength of the welded joint. The results showed that the relationship between friction time and ultimate tensile strength is not linear, with the increase in friction time. The increasing of friction time, caused the ultimate tensile strength increase to a maximum value and then the ultimate tensile strength of the joint will decrease sharply. The greatest ultimate tensile strength is obtained at a friction time 9 seconds, with ultimate tensile strength 111.89 MPa